WALL MAGAZINE AS MEDIA IN GRASPING PUPILS’ READING INTEREST AT PRIMARY LEVEL - Diah Astuty; Fathurrahman Fathurrahman (Jo-ELT (Journal of English Language Teaching) Fakultas Pendidikan Bahasa & Seni Prodi Pendidikan Bahasa Inggris IKIP, 2018)
The paper aims to describe the literacy movement initiated by Indonesian Government. Since there is disproportional distribution of literacy exposures between the pupils who are living in urban areas and the pupils who are living in rural areas, it needs important roles of teachers and school managements mainly for those at rural areas in developing and improving reading habits for their pupils. The wall magazines can be used as affordable media in grasping pupils’ reading interest at primary level. The appropriate procedures in using wall magazines at primary schools can support divergent purposes to make the pupils get interested in reading. The use of wall magazines is also intended to create reading environment for the pupils in order to learn and apply the literacy movement program at early level. The appropriate use of strategies in using wall magazine is planned to train the pupils learning how to read and think critically about the textual materials that are provided by using attractive and appropriate visual mode. The study would be conducted as case-study in describing the procedures and the use of wall magazine at SDN Pamolokan 3 at Sumenep as a part of  Literacy Movement program at school (which known as Gerakan Literasi Sekolah or GLS). The data of this study would be qualitative data in the forms of questionnaires results and interviews.